End‐Stage Renal Disease in an Infant With Hajdu‐Cheney Syndrome. Issue 3 (June 2016) - Battelino, Nina; Writzl, Karin; Bratanič, Nevenka; Irving, Melita D; Novljan, Gregor
Abstract: Hajdu‐Cheney syndrome (HJCYS) is a rare, autosomal dominant, skeletal disorder caused by mutations in the NOTCH2 signaling pathway for which genetic testing has recently become available. Renal abnormalities are associated in at least 10% of cases. We present an 8‐year‐old Caucasian boy, born with multiple dysmorphic features consistent with HJCYS. Imaging of the urinary tract revealed bilateral cystic dysplastic kidneys with associated vesicoureteral reflux. Renal function has been impaired since birth and deteriorated progressively to end‐stage renal disease (ESRD) by the age of two and a half years, when peritoneal dialysis was initiated and only recently renal transplantation was performed. Additional congenital abnormalities and multisystem involvement in HJCYS further complicated management, and he developed refractory anemia. Molecular diagnosis was confirmed by identification of a truncating mutation in exon 34 of NOTCH2 . Although, renal abnormalities are considered an integral part of the HJCYS, published reports on ESRD are scarce. In those few published cases, where ESRD was recognized, renal failure developed either in late adolescence or adulthood. This is the first report of early ESRD occurring in a child. Patients with HJCYS may need chronic renal replacement therapy even in early childhood. The management of these children can be challenging given the multisystemic manifestations of HJCYS.